2019
DOI: 10.1089/ped.2018.0964
|View full text |Cite
|
Sign up to set email alerts
|

Early Stage Impacts of Adenoidectomy With/Without Tonsillectomy on Immune Functions of Children Aged Less Than Three Years

Abstract: To evaluate the early stage effects of adenoidectomy with/without tonsillectomy on immune functions in children aged <3 years. Methods: Twenty-four children aged <3 years underwent adenoidectomy with/without tonsillectomy were included. The levels of IgG, IgA, IgM, C3, and C4 were measured for humoral immunity, and the levels of CD3 + , CD4 + , CD8 + , CD19 + , CD56 + , CD3 + CD4-CD8-, and CD3 + CD4 + CD8 + T cells were measured for cellular immunity before and 2 weeks after the operation. Results: The postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Whenever left untreated, AH may prompt obstructive sleep apnea (snuffling, uneasiness, mouth breathing), ear issues, pulmonary hypertension, craniofacial peculiarities and inability to thrive. 2 However, diagnosis can be thought provoking in a patient with AH symptoms. There are list of recommendations for the diagnosis of AH but recent studies suggested that X-rays soft tissue neck lateral view and nasal endoscopy either rigid or flexible are the gold standard investigations for AH diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever left untreated, AH may prompt obstructive sleep apnea (snuffling, uneasiness, mouth breathing), ear issues, pulmonary hypertension, craniofacial peculiarities and inability to thrive. 2 However, diagnosis can be thought provoking in a patient with AH symptoms. There are list of recommendations for the diagnosis of AH but recent studies suggested that X-rays soft tissue neck lateral view and nasal endoscopy either rigid or flexible are the gold standard investigations for AH diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment, particularly adenoidectomy, is recommended for children with snoring. By removing the hypertrophic adenoids, adenoidectomy alleviates nasal congestion and Trop J Pharm Res, February 2024; 23 (2): 364 hypoventilation that occur during sleep at night [4][5][6]. Nasal endoscopic adenoidectomy has become the preferred treatment method for snoring in children due to advancements in nasal endoscope technology.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoid is little in size at earliest stages yet increments in initial four years of life because of the improvement of immunity. Whenever left untreated, Adenoid Hypertrophy may prompt obstructive sleep apnea (snuffling, rest uneasiness, mouth breathing), ear issues, pulmonary hypertension, craniofacial peculiarities and inability to thrive [2]. In any case, the conclusion can be provocative in patients with manifestations of AH.…”
Section: Introductionmentioning
confidence: 99%